Cytokinins Stimulate Plasmodesmatal Transport in Leaves - Horner, Wilson; Brunkard, Jacob O. (Frontiers in Plant Science, 2021)
Plant cells are connected by plasmodesmata (PD), nanoscopic channels in cell walls that allow diverse cytosolic molecules to move between neighboring cells. PD transport is tightly coordinated with physiology and development, although the range of signaling pathways that influence PD transport has not been comprehensively defined. Several plant hormones, including salicylic acid (SA) and auxin, are known to regulate PD transport, but the effects of other hormones have not been established. In this study, we provide evidence that cytokinins promote PD transport in leaves. Using a green fluorescent protein (GFP) movement assay in the epidermis of Nicotiana benthamiana, we have shown that PD transport significantly increases when leaves are supplied with exogenous cytokinins at physiologically relevant concentrations or when a positive regulator of cytokinin responses, ARABIDOPSIS HISTIDINE PHOSPHOTRANSFER PROTEIN 5 (AHP5), is overexpressed. We then demonstrated that silencing cytokinin receptors, ARABIDOPSIS HISTIDINE KINASE 3 (AHK3) or AHK4 or overexpressing a negative regulator of cytokinin signaling, AAHP6, significantly decreases PD transport. These results are supported by transcriptomic analysis of mutants with increased PD transport (ise1–4), which show signs of enhanced cytokinin signaling. We concluded that cytokinins contribute to dynamic changes in PD transport in plants, which will have implications in several aspects of plant biology, including meristem patterning and development, regulation of the sink-to-source transition, and phytohormone crosstalk.